Sistem Informasi Pelayanan Jasa Notaris Menggunakan PHP dan MySQL di Kantor Notaris Kusliana S.H., M.Kn - Shinta Esabella; Hanif Fauzan Ramadhan; Farida Idifitriani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Abstract−This study aims to make it easier for prospective clients to be able to find out service information and requirements at the notary's office, making it easier for prospective clients to make a service without having to come to the notary's office. The software development method used is waterfall and uses a structured development method and is built using the PHP programming language, and database processing using MySQL, using the blackbox testing method, namely testing carried out by testing the software in terms of functionality. The results of the research are Notary Services Information System Using PHP and MySQL at Notary Office Kusliana S.H., M.Kn. This is expected to provide information and convenience for prospective clients to find out service information and requirements and can apply for services without coming to the notary's office.